2007
DOI: 10.1111/j.1365-2648.2007.04120.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a reflective learning intervention to improve critical thinking in novice nurses

Abstract: Used as a reflective practicum, contextual learning can be a model of clinical learning in nursing education that develops the contextual, reflective nature of critical thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 43 publications
(42 reference statements)
6
65
0
3
Order By: Relevance
“…15 Similarly, athletic training preceptors often use a variety of teaching strategies with their students in the clinical setting, including hands-on activities and asking a variety of clinical questions. 13 Additionally, clinical case discussions, 16 encouraging student reflection, 17 and questioning have been used as methods of developing critical thinking skills. 18 Providing preceptors with specific strategies to help develop their students' critical thinking skills could help them better understand the techniques they already incorporate into their clinical teaching and provide additional methods for developing students.…”
Section: Teaching and Learning In The Clinical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Similarly, athletic training preceptors often use a variety of teaching strategies with their students in the clinical setting, including hands-on activities and asking a variety of clinical questions. 13 Additionally, clinical case discussions, 16 encouraging student reflection, 17 and questioning have been used as methods of developing critical thinking skills. 18 Providing preceptors with specific strategies to help develop their students' critical thinking skills could help them better understand the techniques they already incorporate into their clinical teaching and provide additional methods for developing students.…”
Section: Teaching and Learning In The Clinical Settingmentioning
confidence: 99%
“…[16][17][18] Preceptors can guide discussions about patient cases with their students, 16 as well as pose questions regarding those cases that encourage students to analyze the information and come to a decision. 18 One suggested method for facilitating discussion between preceptor and student is the One-Minute Preceptor method.…”
Section: Teaching and Learning In The Clinical Settingmentioning
confidence: 99%
“…At the end of a case study undertaken in a clinical setting aimed at evaluating a reflective practice intervention with six dyads composed of a novice nurse and a tutor, Forneris and Peden-McAlpine observed that novice nurses had developed critical thinking abilities. It would appear, then, that reflective practice could be used to develop certain skills necessary for nursing practice [22] .…”
Section: Literaturementioning
confidence: 99%
“…In summary, reflection has been shown to benefit nursing practices (Forneris & Peden-McAlpine, 2007;Freshwater, 2008;Glasson et al, 2006;Taylor, 2006;Taylor et al, 2008a can be examined and explored within the contexts of care. By encouraging nurses to use reflective processes in their practice, they can be supported to identify their attitudes, influences, experiences and concerns, for example, in end of life care in residential aged care facilities, while establishing a foundation on which they can examine future care for the dying.…”
Section: Reflection In Nursingmentioning
confidence: 99%